2010
DOI: 10.29087/2010.2.1.06
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Libraries in Terms of Learning and Working Collaboratively: An Interview with Mary Somerville

Abstract: Editors of Collaborative Librarianship (CL) recently sat down with Dr. Somerville to explore aspects of her fascinating new book, Working Together: Collaborative Information Practices for Organizational Learning (Chicago: ACRL, 2009), that deal with collaboration and rethinking the purpose and structures of the academic library. CL welcomes your response to any part of this interview. A critical review of this book will be in an upcoming issue of Collaborative Librarianship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Finally, the desirability of embedding opportunities for information literacy learning into the subject teaching context (Barbour et al ., ) means that academics and librarians need to work collaboratively in order to design effective learning environments. This calls for collaboration, which involves ‘inviting the ideas and talents of others into decision making and action taking …[and] … requires appreciating the value of a wide range of knowledge, skills, and abilities to achieve a common good’ (Somerville et al ., , p. 38).…”
Section: Up‐skilling and Cross‐boundary Trends In Academic Workmentioning
confidence: 95%
“…Finally, the desirability of embedding opportunities for information literacy learning into the subject teaching context (Barbour et al ., ) means that academics and librarians need to work collaboratively in order to design effective learning environments. This calls for collaboration, which involves ‘inviting the ideas and talents of others into decision making and action taking …[and] … requires appreciating the value of a wide range of knowledge, skills, and abilities to achieve a common good’ (Somerville et al ., , p. 38).…”
Section: Up‐skilling and Cross‐boundary Trends In Academic Workmentioning
confidence: 95%
“…One the other hand, another interviewee, a municipal (single-tier) and regional (upper-tier) councillor for Acton, in Halton Region, Clark Somerville, was not opposed to Highway 413 and, similarly, was highly deferential to the Province. Despite this deference, Mr. Somerville also proposed that environmental conservation is "best done at a watershed level" because "doing a regionallevel project is cheaper, and there's an economy of scale" (Somerville, 2023). This perspective was echoed by Colin Best, Regional Councillor for Milton in Halton Region; regional governance makes sense for services like water and biodiversity 7 The federal government paused the development of H413 in 2021 due to an investigation into species at risk along the proposed route, including in the Greenbelt (Callan & D'Mello, 2023).…”
Section: Greater Toronto Highway 413 and Political Economymentioning
confidence: 99%
“…Sommerville suggested that many things don't work at the regional scale, but some things do. These include goods like "water, wastewater, and transit" (Somerville, 2023). This is something that Mr. Somerville critiqued regionally, insofar as there is a lack of coherence between municipalities on regional issues like wastewater filtration.…”
Section: Greater Toronto Highway 413 and Political Economymentioning
confidence: 99%
See 1 more Smart Citation